Manufacturing Process and Benefits of Glass-Ceramics from Basalt Rocks - sugiyanto, sugiyanto (Universitas Muhammadiyah Metro, 2024)
As a means of promoting national independence, the growing usage of dental implants must be bolstered by the advancement of indigenous materials. Indonesia possesses many natural resources that could be utilized as a material for dental implants. Bioceramic materials, which include bioactive, bioresorbable, and bioinert materials, can be used for dental implants. Glass-ceramics from basalt rocks are currently regarded as one of the bioactive materials of interest. In this review article, various techniques for turning basalt into glass-ceramics are discussed. By using glass-ceramics from basalt rocks as a potential supply of dental implant materials, a country's independence and the welfare of its citizens will be supported.